To find the quadratic equation in intercept form \( y = a(x - p)(x - q) \), where \( p \) and \( q \) are the x-intercepts, we can start by using the given x-intercepts at (2, 0) and (4, 0). Thus, we have:
\[ y = a(x - 2)(x - 4) \]
Next, we need to determine the value of \( a \) using the third point (5, 6). We can substitute \( x = 5 \) and \( y = 6 \) into the equation:
\[ 6 = a(5 - 2)(5 - 4) \]
This simplifies to:
\[ 6 = a(3)(1) \] \[ 6 = 3a \]
Now, solving for \( a \):
\[ a = \frac{6}{3} = 2 \]
Now we substitute \( a \) back into our intercept form equation:
\[ y = 2(x - 2)(x - 4) \]
Thus, the quadratic equation that accurately represents the given information is:
\[ y = 2(x - 2)(x - 4) \]
So, the correct response is:
y = 2(x - 2)(x - 4)